INFLUENZA PANDEMIC: FACTS AND SUGGESTIONS - Yu.Z. Gendon (Педиатрическая фармакология)
The review highlights data on the influenza pandemic in 1918, 1957, 1968, 1977 and virus strain properties, which caused them. The author considers genesis mechanisms of the pandemic flu strains, including mutations, resulting into the increase of virulence, as well as an opportunity for the process of the human and bird flu reas sortion to take part in the genesis of the pandemic strains. The author also examines the mechanisms for turning low virulent flu viruses into high virulent ones able to induce epizootic outbreaks. The work discusses genes and proteins, defining specific character of the avian flu viruses and probable H5N1 flu pandemic appearance. The author thinks it quite unlikely for such an event to occur.Key words: flu, pandemic.